Art Space in Intermedial Context (poetry and fine arts) - Mocherniuk, Natalia (Pitannâ lìteraturoznavstva, 2013)
The article is dedicated to the investigation of space in literature. Space and time are basic criteria in the classification of arts. The author pays attention to approaches of structuralism, semiotics, phenomenology, sociology in the investigation of art space. Intermedial analysis of space poetics can combine with other methods of philological science. The principles of intermedial methodology in analysis of spatial characteristic of the literary work are defined. According to the typology, founded on the interpretation of relations in the semiotic triangle, there are three types of intermedial connections. Firstly, there is a model of the material construction of another kind of art, for example visual forms in poetry. Secondly, the projection of visual art creative rules into poetry. To my mind, it is the most difficult type of intermedial connection. Thirdly, incorporation of images, painting, drawing, sculpture and architecture plots into literature, for example genre of ekphrasis. Therefore space and time inversions are characteristic for each type of intermedial connections. The material of the investigation is the poetry of Ukrainian artists of the period between the two world wars. The poetry by S. Hordyns’kyi, V. Havryliuk, V. Khmeliuk demonstrates various modes of a space presentation in the intermedial aspect.